Solve all your doubts with Teachoo Black (new monthly pack available now!)

Examples

Example 1

Example 2 Important

Example 3 Important

Example 4

Example 5 Important Deleted for CBSE Board 2023 Exams

Example 6 Important Deleted for CBSE Board 2023 Exams

Example 7 Deleted for CBSE Board 2023 Exams

Example 8 Important Deleted for CBSE Board 2023 Exams You are here

Example 9 Deleted for CBSE Board 2023 Exams

Example 10 Important Deleted for CBSE Board 2023 Exams

Example 11 Important Deleted for CBSE Board 2023 Exams

Example 12 Deleted for CBSE Board 2023 Exams

Example 13 Important Deleted for CBSE Board 2023 Exams

Example 14 Important Deleted for CBSE Board 2023 Exams

Example 15 Important Deleted for CBSE Board 2023 Exams

Example 16 Deleted for CBSE Board 2023 Exams

Example 17 Important Deleted for CBSE Board 2023 Exams

Last updated at Sept. 3, 2021 by Teachoo

Example 8 The second, third and fourth terms in the binomial expansion (x + a)n are 240, 720 and 1080, respectively. Find x, a and n. We know that general term of (a + b)n is Tr+1 = nCr (a)n-r . (b)r Given that second term of (x + a)n is 240 i.e. T2 = 240 T1+1 = 240 Putting r = 1 , a = x & b = a T1+1 = nCr (x)n-1 (a)1 T2 = nCr xn-1a 240 = nCr xn-1a Similarly, Third term of (x + a)n is 720 i.e. T3 = 720 T2+1 = 720 Putting r = 2 , a = x &b = a in (1) T2+1 = nC2 (x)n – 2. (b)2 720 = nC2 xn – 2.a2 Also , Fourth term of (x + a)n is 1080 i.e. T4 = 1080 T3+1 = 1080 Putting r = 3 , a = x & b = a in (1) T3+1 = nC3 xn – 3 . a3 1080 = nC3 xn – 3 . a3 Dividing (3) by (2) 720/240 = (𝑛𝐶2 𝑥^(𝑛 − 2) 𝑎^2)/(𝑛𝐶1 〖𝑥 〗^(𝑛 −1 ) 𝑎) 3 = (𝑛𝐶2 )/(𝑛𝐶1 ) × ( 𝑥^(𝑛−2) )/𝑥^(𝑛−1 ) × ( 𝑎^2)/𝑎 3 = (𝑛!/2!(𝑛−2)!)/(𝑛!/1!(𝑛−1)!) × xn – 2 – (n – 1) × a1 3 = 𝑛!/2!(𝑛−2)! "×" (1!(𝑛−1)! )/𝑛! × xn – 2 – n + 1 × a 3 = 𝑛!/2(𝑛−2)! "×" (1(𝑛−1)(𝑛−2)! )/𝑛! × x–1 × a 3 = ((𝑛−1) )/2 × 𝑎/𝑥 3 × 2 = (n – 1) × 𝑎/𝑥 6 = (n – 1) × 𝑎/𝑥 6/(𝑛 − 1) = 𝑎/𝑥 Now Dividing (4) by (3) 1080/720 = (𝑛𝐶3 𝑥^(𝑛−3) 𝑎^3)/(𝑛𝐶2 〖𝑥^(𝑛−2 ) 𝑎〗^2 ) 3/2 = (𝑛𝐶3 )/(𝑛𝐶2 ) × ( 𝑥^(𝑛−3) )/𝑥^(𝑛−2 ) × 𝑎^3/𝑎^2 3/2 = (𝑛!/3!(𝑛−3)!)/(𝑛!/2!(𝑛−2)!) × xn – 3 – (n – 2) × a3 – 2 3/2 = 𝑛!/3!(𝑛 −3)! × 2!(𝑛−2)!/𝑛! × x-1 × a1 3/2 = 𝑛!/(3(2)!(𝑛 −3)!) × (2!(𝑛−2)(𝑛−3)!)/𝑛! × 𝑎/𝑥 3/2 = ((𝑛 −2))/3 × 𝑎/𝑥 9/(2(𝑛 −2)) = 𝑎/𝑥 Now our equations are 6/(𝑛 − 1) = 𝑎/𝑥 …(A) 9/(2(𝑛 − 2)) = 𝑎/𝑥 …(B) Equating (A) & (B) 9/(2(𝑛 −2)) = 6/(𝑛 −1) 9 × (n – 1) = 6 × 2(n – 2) 9n – 9 = 12n – 24 –9 + 24 = 12n – 9n 15 = 3n 15/3 = n 5 = n n = 5 Putting n = 5 in (A) 6/(𝑛 − 1) = 𝑎/𝑥 6/(5 − 1) = 𝑎/𝑥 6/4 = 𝑎/𝑥 3/2 = 𝑎/𝑥 3x = 2a (3/2)x = a a = (3/2)x Putting n = 5, a = (3/2)x in (2) 240 = nCr xn − 1 a 240 = 5C1 x5 − 1 . (3/2)x 240 = 5!/(1 × 4!) x4 . (3/2)x 240 = 5!/(1 × 4!) x4 . (3/2)x 240 = (5 × 4!)/4! x4 . (3/2)x 240 = 5x4(3/2)x 240 = (5 × 3)/2 × x5 (240 × 2)/(5 × 3) = x5 32 = x5 x5 = 32 x5 = (2)5 x = 2 Putting x = 2 in 𝑎/𝑥 = 3/2 𝑎/2 = 3/2 a = 3 Hence, x = 2, a = 3, n = 5